Chinese water culture and implications for cruise tourism – a five-dimension framework. (1st January 2012) - Fu, Xiaoxiao; Huang, Zhuowei; Cai, Liping A.
This study aims to examine the Chinese values and beliefs of water and provide insights into the Chinese market of cruise tourism. Chinese classical works on water are reviewed and synthesised through both cultural and historical angles, based on which a five-dimension framework is proposed on Chinese water culture in relation to cruise tourism. The five dimensions are origin of life, sustained energy, purity, freshness, and natural state of being . Two propositions are postulated to suggest Chinese tourists' expectations and p for cruise vacations. Implications for the cruise industry are discussed. The study informs researchers and practitioners of unique perspectives in understanding Chinese tourists' motivations, perceptions, expectations, preferences, and decision-making process, particularly for the cruise sector that witnesses a booming Chinese market.